Radio propagation and remote sensing of the environment. - Armand, N. A., ....-; Polyakov, V. M., ....- (Boca Raton : CRC, 2005)
Describes the processes of radio propagation and analyzes the problems that enable estimation of media Reviews formulations and basic principles of remote sensing problems Examines the various types of microwave remote sensing equipment as well as the connection between target data and the researched environment Covers the distinctive features of remote methods applied to different natural media The emergence of microwave technology in the field of remote sensing creates a need to understand the mechanisms of radio propagation and the interaction between waves and surrounding media. Radio Propagation and Remote Sensing of the Environment describes the processes of radio propagation and analyzes the problems that enable estimation of media. The book begins by exploring propagation processes and related phenomena including absorption, refraction, reflection, and scattering. This discussion demonstrates the relationship between radiowave parameters of amplitude, phase, frequency, and polarization and media characteristics such as permittivity and shape. The volume presents equations that enable the estimation of the strength of various effects, as well as the detection of these effects against a background of various masking phenomena. The second part of this book analyzes how knowledge of radiowave properties allows accurate estimations of media via what were formerly known as inverse problems. The text examines the empirical methods that interpret remote sensing data, and how they are applied in the creation of useful approximation models. The authors also describe the operational principles of microwave devices used in remote sensing, and provide insight into the stabilizing a priori information that greatly increases the accuracy of remote sensing solutions.
Keywords: Radiogolfvoortplantingen; Remote sensing